2014
DOI: 10.13183/jcrg.v3i0.75
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pay-for-Performance on Efficiency and Effectiveness in Hospitals: A Systematic Review

Abstract: Ab s t r a c tPurpose: Pay-for-performance (P4P) refers to the transfer of money on taking a measurable action or achieving a predetermined performance target. In this systematic review, we will present the results of P4P impacts based on published articles. Methods:A systematic review of literature was done using following databases and search engines: PubMed, Web of knowledge, Sciencedirect, The Cochrane library, MagIran and SID. Keywords used were, Pay-for-performance, P4P, output based payment, result base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…In the same year, Glickman et al published a study on quality improvement, using the reward-based P4P for cardiac patients, while studying 54 American hospitals participating in a federally funded P4P pilot project, compared to 446 control hospitals, and found that the program did not appear to impact quality of care [16]. A few years later, a multicountry meta-analysis of P4P was conducted, yielding similarly contradictory results and ultimately concluding that P4P effects can vary widely, depending on the specific analyzed instance and on a number of contextual factors, such as the relative magnitude of the incentives, how the target goals were measured, the length of the intervention, and the type of medical treatment sought [17]. Due to the wide range of contexts found in the thirty-four studies selected for analysis, the authors do not offer specific recommendations as to which combination of factors may be most effective, as data are still lacking to provide this type of foundational hypothesis [17].…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same year, Glickman et al published a study on quality improvement, using the reward-based P4P for cardiac patients, while studying 54 American hospitals participating in a federally funded P4P pilot project, compared to 446 control hospitals, and found that the program did not appear to impact quality of care [16]. A few years later, a multicountry meta-analysis of P4P was conducted, yielding similarly contradictory results and ultimately concluding that P4P effects can vary widely, depending on the specific analyzed instance and on a number of contextual factors, such as the relative magnitude of the incentives, how the target goals were measured, the length of the intervention, and the type of medical treatment sought [17]. Due to the wide range of contexts found in the thirty-four studies selected for analysis, the authors do not offer specific recommendations as to which combination of factors may be most effective, as data are still lacking to provide this type of foundational hypothesis [17].…”
Section: Main Textmentioning
confidence: 99%
“…A few years later, a multicountry meta-analysis of P4P was conducted, yielding similarly contradictory results and ultimately concluding that P4P effects can vary widely, depending on the specific analyzed instance and on a number of contextual factors, such as the relative magnitude of the incentives, how the target goals were measured, the length of the intervention, and the type of medical treatment sought [17]. Due to the wide range of contexts found in the thirty-four studies selected for analysis, the authors do not offer specific recommendations as to which combination of factors may be most effective, as data are still lacking to provide this type of foundational hypothesis [17]. As mentioned previously, the magnitude of the offered financial incentive may be one of those factors influencing outcomes of P4P practices.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation